2020
DOI: 10.1093/noajnl/vdaa121
|View full text |Cite
|
Sign up to set email alerts
|

OptimalTTF-1: Enhancing tumor treating fields therapy with skull remodeling surgery. A clinical phase I trial in adult recurrent glioblastoma

Abstract: Background Preclinical studies suggest that skull remodeling surgery (SR-surgery) increases the dose of tumor treating fields (TTFields) in glioblastoma (GBM) and prevents wasteful current shunting through the skin. SR-surgery introduces minor skull defects to focus the cancer-inhibiting currents towards the tumor and increase the treatment dose. This study aimed to test the safety and feasibility of this concept in a phase 1 setting. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…For superficial tumors, removal of a standard craniotomy bone flap increased the electrical field strength by up to 70% ( 51 ). A phase 1 safety study on 15 patients with recurrent GBM confirmed the safety of this approach ( 52 ) and a phase 2 study was announced ( 53 ).…”
Section: Discussionmentioning
confidence: 93%
“…For superficial tumors, removal of a standard craniotomy bone flap increased the electrical field strength by up to 70% ( 51 ). A phase 1 safety study on 15 patients with recurrent GBM confirmed the safety of this approach ( 52 ) and a phase 2 study was announced ( 53 ).…”
Section: Discussionmentioning
confidence: 93%
“…The tumors were all near the surface of the brain and 4 patients did not receive TTFields due to personal reasons. Three drilling patterns were applied with signi cantly prolonged median progression free survival (mPFS) and mOS (mPFS, 4.6 months; 6-month PFS rate, 36%; mOS, 15.5 months) 29 . To clarify the exact augmentation of SR surgery to TTFields, one phase II clinical trial (NCT04223999) is ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Korshoej AR et al conducted in vitro simulation studies to prove that the skull remodeling (SR) by drilling, thinning, and craniectomy could intensify the local dosage. And they recently published the results of their phase I trial entitled OptimalTTF-1, in which SR surgery combined with TTFields and the physicians' choice of cancer treatment could elongate the survival of recurrent GBM patients, compared to historical cohorts 29 . Nevertheless, more detailed research on the modulations of SR surgery is required.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was proposed to introduce holes at strategic positions in the skull (skull-remodeling surgery, SR-surgery) to facilitate current flow into the tumor, and thereby enhance the anti-neoplastic dose of TTFields focally in the region of interest (Korshoej et al, 2016 ). The principle has been described and analyzed in preclinical modeling studies (Korshoej et al, 2018 ; Mikic and Korshoej, 2021 ) and the concept translated into a phase 1 clinical trial demonstrating safety in 15 patients with recurrent GBM (Korshoej et al, 2020 ). Furthermore, the trial indicated prolonged overall survival (15.5 months) relative to 6–11 months in comparable first recurrence GBM trial population (Taal et al, 2014 ) and showed that an average of 32% (range 25–59%) field enhancement could be obtained with an mean skull defect area of 10.5 cm 2 (range 7–48 cm 2 ).…”
Section: Introductionmentioning
confidence: 99%